Information communications technology (ICT) use and perceived impact on learning among post graduate students of Olabisi Onabanjo university, Ago-Iwoye (2008)
This paper examines Information Communications Technology (ICT) use and perceived impact on learning among post graduate students of Olabisi Onabanjo University (OOU), Ago-Iwoye.. A descriptive survey research method was adopted for the study. A total of One Hundred (100) respondents were selected from the institution using simple random sampling technique. The level of usage of Information and Communications Technology (ICT), in teaching and learning was examined. Questionnaire was used to collect gather data from the respondents who participated in the study. The data collected were analyzed, using frequency grade tabulations and t-test statistical method. The results of the analysis indicated that there is a significant impact of Information and Communications Technology (ICT) use on teaching and learning.. Result also showed that there is a significant improvement on the part of the students and lecturers in using ICTs in teaching and learning activities of Olabisi Onabanjo University postgraduate students.